German registry of paediatric deep brain stimulation in patients with childhood-onset dystonia (GEPESTIM). (January 2017) - Koy, A.; Weinsheimer, M.; Pauls, K.A.M.; Kühn, A.A.; Krause, P.; Huebl, J.; Schneider, G.-H.; Deuschl, G.; Erasmi, R.; Falk, D.; Krauss, J.K.; Lütjens, G.; et al.
Abstract: Background: Data on paediatric deep brain stimulation (DBS) is limited, especially for long-term outcomes, because of small numbers in single center series and lack of systematic multi-center trials. Objectives: We seek to systematically evaluate the clinical outcome of paediatric patients undergoing DBS. Methods: A German registry on paediatric DBS (GEPESTIM) was created to collect data of patients with dystonia undergoing DBS up to the age of 18 years. Patients were divided into three groups according to etiology (group 1 inherited, group 2 acquired, and group 3 idiopathic dystonia). Results: Data of 44 patients with a mean age of 12.8 years at time of operation provided by 6 German centers could be documented in the registry so far (group 1 n = 18, group 2 n = 16, group 3 n = 10). Average absolute improvement after implantation was 15.5 ± 18.0 for 27 patients with pre- and postoperative Burke-Fahn-Marsden Dystonia Rating scale movement scores available (p < 0.001) (group 1: 19.6 ± 19.7, n = 12; group 2: 7.0 ± 8.9, n = 8; group 3: 19.2 ± 20.7, n = 7). Infection was the main reason for hardware removal (n = 6). 20 IPG replacements due to battery expiry were necessary in 15 patients at 3.7 ± 1.8 years after last implantation. Discussion: Pre- and postoperative data on paediatric DBS are very heterogeneous and incomplete but corroborate the positive effects of DBS on inherited and acquired dystonia. Adverse events including relatively frequent IPG replacements due to battery expiry seem to be a prominent feature of children with dystonia undergoing DBS. The registry enables collaborative research on DBS treatment in the paediatric population and to create standardized management algorithms in the future. Highlights: First German registry on short- and long-term effects of DBS in paediatric patients. "Clinical data" generated by this multicenter cooperation confirms DBS-effects reported by monocenter settings. Adverse events among children are higher compared to adult patients undergoing DBS. Collected data helps to establish eligibility criteria and management algorithms. Registry enables to do collaborative research on paediatric DBS.